Gamification-Based Learning in Science Education to Enhance Student Engagement, Scientific Literacy, and Critical Thinking Skills - Utami, Ayu Rischi (Scientica Education Journal, 2024)
This study aims to examine the effectiveness of gamification-based learning in enhancing students’ engagement, scientific literacy, and critical thinking skills in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using gamification-based learning and a control group taught using conventional methods. Data were collected through a student engagement questionnaire, a scientific literacy test, and a critical thinking skills test. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, gamification-based learning significantly improved students’ engagement across cognitive, emotional, and behavioral dimensions, as well as their abilities in analysis, evaluation, and problem-solving. These findings suggest that gamification is an effective instructional strategy for promoting meaningful learning and developing essential 21st-century competencies in science education